RESEARCH REGARDING THE DETERMINATION OF THE MAIN PHYSICAL PROPERTIES OF THE FĂGET GLEY SOIL, TIMIȘ COUNTY, IN STRAWBERRY CROPS - Amurtiya MICHAEL; Abdu Karniliyus TASHIKALMA; Ahmadu Abubakar TAFIDA; Mark POLYCARP (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objectives of the papers were to characterize the natural framework, to identify and characterize the soil types and subtypes, to determine the physical properties of luvosoil in the Faget area, Timis County, Romania in strawberry crops. The physical properties of the gley soil were determined based on soil samples collected from a natural setting, on two depth levels, namely: 0-10 and 10-20 cm, during two various periods of the year, respectively, early spring, during March and autumn, during October. The research was carried out during two years, namely: 2013 and 2014, managing the following analyses, and the following methods: soil density; apparent density; total porosity and aeration porosity. The soil density registered values ranging from 2.43 g/cm3, at the 0-10 cm depth and 2.48 g/cm3, at the 10-20 cm depth. The soil apparent density registered values ranging from 1.16 g/cm3, at a 0-10 cm depth, in March 2013 and 1.20 g/cm3, at a 10-20 cm depth, in October. The total soil porosity presented values ranging from 41%, at a 10-20 cm depth, in October 2014 and 45%, at a 0-10 cm depth, in March 2013 and 2014. The soil aeration porosity presented values ranging from 10.90%, at a 10-20 cm depth, in October 2014 and 13.90%, at a 0-10 cm depth, in March 2013.